DIGITAL STORYTELLING IN READING LITERACY: A STUDY OF STUDENTS PERCEPTIONS AND EXPERIENCES - Ropiul Umam; Imro'atul Husna Afriani; Rizki Nurfida Pambayun (Universitas PGRI Palembang, 2025)
This study explores junior high school students’ perceptions and experiences regarding the use of digital storytelling in English reading instruction, specifically in the context of descriptive texts. The primary aim is to examine how digital storytelling affects students’ reading comprehension, motivation, and engagement. Using a qualitative descriptive method, data were gathered through Likert-scale questionnaires and semi-structured interviews involving 15 eighth-grade students from SMP Muhammadiyah 7 Sempu. Thematic analysis supported by triangulation revealed that over 69.70% of respondents expressed positive or neutral views toward digital storytelling, based on responses to 16 questionnaire items. In addition, data from 10 interview questions indicated that multimedia elements like images and audio significantly improved students' understanding and memory retention, while also boosting their motivation and interest in reading. Although some students reported challenges with vocabulary and reading confidence, the majority expressed a preference for digital storytelling over conventional approaches. These findings suggest that digital storytelling holds strong potential as an effective and engaging instructional method for enhancing reading literacy in EFL settings.